Implementation Of Quizizz-Based Learning Media In General English Lessons In The Stkip Al Maksum Elementary School Teacher Education Study Program - Supriadi (LPPM STKIP AL MAKSUM, 2020)
This study investigates the utilization or implementation of Quizizz, an internet-based questionnaire platform, as an instructional tool for general English courses in the STKIP AL Maksum Primary School Teacher Education Study Program. The objective of this study is to examine the media planning procedure, its execution, and the determinants that impact the utilization of Quizizz. This study employs a qualitative descriptive methodology and collects data through triangulation techniques, including documentation, interviews, and observation. Quizizz is a game-based learning platform that enhances student engagement and offers adaptable assessment alternatives, according to the literature review. The results of studies indicate that Quizizz has a beneficial impact on student motivation by enhancing the relevance and interest of the learning process. In spite of this, obstacles associated with technological infrastructure must be taken into account in order to achieve maximum efficacy. This study enhances comprehension regarding the incorporation of technology in English education, placing particular emphasis on the significance of cutting-edge learning tools like Quizizz in contemporary educational advancements. Key words: Quizizz, Media, General English.